Voices from immigrant’s search for security and social protection in Lisbon, Portugal: https://doi.org/10.53809/TS_ISS_2023_n.4_7-32 (Revista "Temas Sociais", 2023)
This article aims to reveal the experiences of immigrants living in Lisbon and examines how the Portuguese social welfare system supports the welfare needs of immigrants., Portugal operates a mixed welfare system where the state finances semi-formal and informal networks operating at macro, meso, and micro levels, and these combine to address immigrants’ challenges. This is a qualitative in-depth study, that focused on eight English-speaking immigrants who use welfare services in two non-governmental organisations in Lisbon. We wanted to know the process of settling in Lisbon, the risks and vulnerabilities, and the main challenges faced when accessing welfare services from public and semi-public actors. The results show that despite Portugal having policies and exceptional interventions that would otherwise promote the well-being of immigrants, immigrants continue to face immense difficulties in entry and when settling. The difficulties in accessing documentation and neo-liberal policies of the state are the major obstacles to the well-being of immigrants in Portugal, as they not only perpetuate reduced social benefits but also proliferate social exclusion. There is a need for a more open and frank discussion on social immigration policies with a firm focus on social interventions, policy frameworks, and implementation to address the relentless challenges of immigrant social protection, is important.
Keywords: Inmigrantes, Bienestar Social, Seguridad, Protección social